Berkovich Nanoindentation on AlN Thin Films - Jian Sheng-Rui; Chen Guo-Ju; Lin Ting-Chun (Nanoscale Research Letters, 2010)
Abstract Berkovich nanoindentation-induced mechanical deformation mechanisms of AlN thin films have been investigated by using atomic force microscopy (AFM) and cross-sectional transmission electron microscopy (XTEM) techniques. AlN thin films are deposited on the metal-organic chemical-vapor deposition (MOCVD) derived Si-doped (2 × 1017 cm−3) GaN template by using the helicon sputtering system. The XTEM samples were prepared by means of focused ion beam (FIB) milling to accurately position the cross-section of the nanoindented area. The hardness and Young’s modulus of AlN thin films were measured by a Berkovich nanoindenter operated with the continuous contact stiffness measurements (CSM) option. The obtained values of the hardness and Young’s modulus are 22 and 332 GPa, respectively. The XTEM images taken in the vicinity regions just underneath the indenter tip revealed that the multiple “pop-ins” observed in the load–displacement curve during loading are due primarily to the activities of dislocation nucleation and propagation. The absence of discontinuities in the unloading segments of load–displacement curve suggests that no pressure-induced phase transition was involved. Results obtained in this study may also have technological implications for estimating possible mechanical damages induced by the fabrication processes of making the AlN-based devices.